A dual-responsive supramolecular amphiphile based on cucurbit[7]uril/butyrylcholine host–guest molecular recognition. Issue 35 (1st September 2016) - Chen, Rener; Gu, Haining; Qiu, Fangli; Zhou, Qizhong; Li, Rongrong; Ye, Yuyuan; Zhuang, Yuguo; Zhang, Jie; Jiang, Huajiang
Abstract: A host–guest molecular recognition is reported between cucurbit[7]uril and butyrylcholine with the driving forces of hydrophobic and charge-dipole interactions. On the basis of this recognition, an enzyme- and photo-responsive supramolecular amphiphile is fabricated, which self-assembles into vesicles in aqueous solution. The assembly and disassembly of vesicles are successfully employed in stimuli-triggered releases of doxorubicin hydrochloride. Graphical abstract: